Trait emotional intelligence, positive and negative emotions in first and foreign language classes: A mixed-methods approach. (November 2020) - Resnik, Pia; Dewaele, Jean-Marc
Abstract: While an increasing number of studies have cast light on the role of emotional variables in foreign language learning, no work to date has investigated the same learners' emotions in their first language (L1) and foreign language (LX) classes. The present mixed-methods study investigated the emotions of 768 secondary- and tertiary-level students in German language (L1) and English language (LX) classes in the German-speaking world. Statistical analyses revealed both higher anxiety and enjoyment in LX classes than in L1 classes. Additionally, enjoyment and anxiety were negatively correlated in both contexts. Participants' enjoyment and anxiety were positively linked in the L1 and LX. Higher levels of trait emotional intelligence (TEI) were linked to higher levels of L1 and LX enjoyment and lower levels of L1 and LX anxiety. Analysis of qualitative feedback on feelings and emotions experienced in both classes revealed twice as many mentions of fun in LX classes than in L1 classes and three times more mentions of boredom in L1 classes. The findings suggest that learners experience stronger positive and negative emotions in their LX class than in their L1 class and that TEI is an important learner-internal variable which has been linked to better performance.